Cytogenetic analyses in three species of Moenkhausia Eigenmann, 1903 (Characiformes, Characidae) from Upper Paraná River (Misiones, Argentina) - Sánchez, Kevin Imanol (2022)
Moenkhausia Eigenmann, 1903 is one of the most diverse genera within Characidae, being an important component of the Neotropical fish fauna. Three members of this genus were cytogenetically analyzed: M. dichroura Kner, 1858, M. intermedia Eigenmann, 1908 and M. sanctaefilomenae Steindachner, 1907. The three species showed 2n = 50 bi-armed chromosomes (NF = 100) and different karyotype formulas: 22m + 22sm + 6st in M. dichroura, 16m + 28sm + 6st in M. intermedia, and 12m + 32sm + 6st in M. sanctaefilomenae. In addition, supernumerary chromosomes (or B-chromosomes) were detected in M. intermedia and M. sanctaefilomenae. C-positive bands were restricted to pericentromeric regions, secondary constrictions and supernumerary chromosomes. Active nucleolus organizer regions (Ag-NORs) and positive CMA3 bands were observed in a single pair of sm chromosomes. Pericentromeric DAPI positive signals were evidenced on chromosomes of M. sanctaefilomenae only. Overall, the three species showed a conservative karyotype macrostructure (diploid number, number of chromosome arms) and variations in microstructure (karyotype formulas, presence/absence of supernumerary chromosomes). We discuss how the observed differences could have been shaped.